2001
DOI: 10.1038/sj.onc.1204075
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis suppressor CC3 inhibits angiogenic properties of tumor cells in vitro

Abstract: Resistance to apoptosis and ability to promote angiogenesis are integral features of the metastatic phenotype. Human gene CC3 is a metastasis suppressor for variant small cell lung carcinoma and a mouse melanoma in vivo. We have shown previously that metastasis-suppressing function of CC3 might be due at least in part to the ability of CC3 protein to predispose tumor cells to apoptosis. Here we demonstrate that CC3 has a previously unidenti®ed eect on the ability of tumor cells to induce angiogenesis in vitro.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
61
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 25 publications
6
61
0
Order By: Relevance
“…TIP30/CC3 has been proposed to function as a metastasis suppressor via its ability to promote apoptosis and inhibit angiogenesis (24 -27). Consistent with this hypothesis, ectopic expression of TIP30 was found to elevate the expression of a subset of proapoptotic genes (27) and angiogenic inhibitors and to downregulate the expression of certain angiogenic stimulators (25). Moreover, deletion of one or both alleles of Tip30 results in spontaneous development of hepatocellular carcinomas and other tumors in mice at a relatively long latency (28).…”
supporting
confidence: 51%
“…TIP30/CC3 has been proposed to function as a metastasis suppressor via its ability to promote apoptosis and inhibit angiogenesis (24 -27). Consistent with this hypothesis, ectopic expression of TIP30 was found to elevate the expression of a subset of proapoptotic genes (27) and angiogenic inhibitors and to downregulate the expression of certain angiogenic stimulators (25). Moreover, deletion of one or both alleles of Tip30 results in spontaneous development of hepatocellular carcinomas and other tumors in mice at a relatively long latency (28).…”
supporting
confidence: 51%
“…2,[7][8][9] The introduction of TIP30 into v-SCLC and other tumor cell lines upregulated expression of a subset of proapoptotic genes and angiogenic inhibitors and down-regulated expression of angiogenic stimulators. 3,8 Thus, TIP30 may suppress tumor growth and metastasis through regulating expression of genes involved in apoptosis and metastasis. Recently, TIP30 was found to interact with coactivator independent of AF-2 function (CIA) and to negatively regulate estrogen receptor ␣-mediated c-myc expression.…”
mentioning
confidence: 99%
“…2 Its expression has been detected in many human normal tissues; however, in some tumor types such as melanoma, breast cancer, neuroblastoma, glioblastoma, colon cancer, and hepatocellular carcinoma, its expression was found to be decreased. [2][3][4][5][6] Studies of Tip30-deficient mice revealed a high incidence of hepatocellular carcinoma and other tumors with a relatively long latency. 6 Expression of TIP30 was reduced in about 33% of surgical specimens from HCC patients.…”
mentioning
confidence: 99%
“…The amino acid sequence of human TIP30 was later confirmed to be identical to that of human CC3 (Xiao et al, 1998). TIP30, which exhibits decreased expression in some cancer cells NicAmhlaoibh and Shtivelman, 2001;Shtivelman, 1997;Tong et al, 2009;Zhao et al, 2006), is a tumor suppressor with proapoptotic activity (El Omari et al, 2005;Xiao et al, 2000;Zhao et al, 2007) as well as with anti-metastatic Shtivelman, 1997;Tong et al, 2009;Xiao et al, 2000;Zhao et al, 2007) and angiogenesis-inhibiting (NicAmhlaoibh and Shtivelman, 2001) properties. TIP30 binds importin-β, which facilitates the cytoplasm-to-nuclear transport of proteins (El Omari et al, 2005;King and Shtivelman, 2004;Zhao et al, 2008), including HuR (Guttinger et al, 2004;Wang et al, 2004).…”
Section: Introductionmentioning
confidence: 95%